Synthetic biology platform for production of novel anthracycline anticancer agents - Wang, Rongbin (fi=Turun yliopisto|en=University of Turku|, 2025)
Anthracyclines, microbial natural products primarily produced by soil-dwelling Streptomyces bacteria, are potent chemotherapeutic agents used clinically worldwide. However, despite their potent antiproliferative activities, their therapeutic application is limited by irreversible cardiotoxicity. Furthermore, their stereochemical complexity hinders the discovery of improved semi-synthetic analogs. Synthetic biology offers a promising alternative for modification of complex natural products. However, this approach is constrained by the lack of a well-established synthetic biology platform tailored for anthracycline biosynthesis. To address these issues, this doctoral thesis establishes a complete synthetic biology platform designed for anthracycline engineering, consisting of an amenable Streptomyces chassis, modular expression vectors, promoters with tunable strengths, efficient terminators, and a curated library of anthracycline biosynthetic genes. To systematically explore anthracycline production, the biosynthetic pathway was redesigned and assembled into four distinct functional modules: (i) polyketide aglycones, (ii) TDP-carbohydrate, (iii) self-resistance and glycosyltransferases, and (iv) post-PKS tailoring, using a standardized BioBricks approach. Initially, the platform was employed to achieve the first complete biosynthesis of three clinically relevant anthracyclines—nogalamycin, doxorubicin, and aclacinomycin. Furthermore, the modular design facilitated combinatorial biosynthesis through strategic mixing and matching of biosynthetic modules. This approach led to the production of 16 anthracycline derivatives, 13 of which are entirely new. The streamlined biosynthetic process and balanced expression enabled efficient downstream purification from small-scale fermentations, which facilitated structural characterization by nuclear magnetic resonance and cytotoxicity test on human cell lines, leading to a discovery of six high potency anthracyclines and giving an insight on structure-activity-relationship of anthracyclines. Overall, this thesis demonstrates the utility of a modular synthetic biology platform for the rational biosynthesis of natural products and the discovery of novel anthracycline analogs, offering a powerful strategy for expanding the structural diversity and therapeutic potential of this important class of anticancer agents.